1994
DOI: 10.1017/s0790966700014841
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric sequelae of MDMA (ecstasy) and related drugs

Abstract: Two cases of psychiatric disorder temporally related to the abuse of hallucinogenic amphetamines 3, 4 methylenedi-oxymethamphetamine (MDMA), methylenedioxyamphetamine (MDA) and methylenedioxyethylamphetamine (MDEA) are described, suggesting that a variety of psychiatric morbidity may be precipitated by abuse of these drugs, including paranoid psychosis, mixed affective psychosis and symptoms of obsessive compulsive disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…There is a growing body of evidence to suggest that this might, indeed, be the case. There are a number of case reports of chronic psychiatric symptoms following regular use of the drug including reports of depersonalisation (McGuire et al 1994), obsessive-compulsive symptoms (Cassidy and Ballard 1994), flashbacks (Creighton et al 1991;McGuire and Fahy 1992;Schifano and Magni 1994), panic attacks (McCann and Ricaurte 1991; Pallantini and Mazzi 1992;McGuire et al 1994;Schifano and Magni 1994;Series et al 1994;Cohen 1996;Windhaber et al 1998), psychosis (Creighton et al 1991;McCann and Ricaurte 1991;McGuire and Fahy 1991;Schifano 1991;Keenan et al 1993;Cassidy and Ballard 1994;McGuire et al 1994) and depression (Benazzi and Mazzoli 1991;McCann and Ricaurte 1991;McGuire et al 1994;Schifano and Magni 1994). These symptoms appear to differ from the more common acute psychiatric effects of ecstasy (Solowji et al 1992;Curran and Travill 1997), in that they were often not associated with the timing of each dose, and were chronic, persisting long after ecstasy use had been discontinued (McGuire 1999).…”
Section: Evidence For Chronic Neuropsychiatric Effectsmentioning
confidence: 99%
“…There is a growing body of evidence to suggest that this might, indeed, be the case. There are a number of case reports of chronic psychiatric symptoms following regular use of the drug including reports of depersonalisation (McGuire et al 1994), obsessive-compulsive symptoms (Cassidy and Ballard 1994), flashbacks (Creighton et al 1991;McGuire and Fahy 1992;Schifano and Magni 1994), panic attacks (McCann and Ricaurte 1991; Pallantini and Mazzi 1992;McGuire et al 1994;Schifano and Magni 1994;Series et al 1994;Cohen 1996;Windhaber et al 1998), psychosis (Creighton et al 1991;McCann and Ricaurte 1991;McGuire and Fahy 1991;Schifano 1991;Keenan et al 1993;Cassidy and Ballard 1994;McGuire et al 1994) and depression (Benazzi and Mazzoli 1991;McCann and Ricaurte 1991;McGuire et al 1994;Schifano and Magni 1994). These symptoms appear to differ from the more common acute psychiatric effects of ecstasy (Solowji et al 1992;Curran and Travill 1997), in that they were often not associated with the timing of each dose, and were chronic, persisting long after ecstasy use had been discontinued (McGuire 1999).…”
Section: Evidence For Chronic Neuropsychiatric Effectsmentioning
confidence: 99%
“…In addition, Creighton et al (1991) reported a patient who was free of psychiatric symptoms for 8 months, but after taking a further 4 doses of Ecstasy the psychological symptoms returned. The individual reported by Cassidy and Ballard (1994) stated that there was a close relationship between symptom improvement and Ecstasy cessation. Additional support comes from a large-scale clinical survey (Schifano et al, 1998), where the longer-term polydrug users, who had consumed an average of 43 Ecstasy tablets, were found to be at a considerably higher risk of developing a psychopathological disorder than the patients who took smaller amounts (average 3).…”
Section: Psychiatric Casesmentioning
confidence: 99%
“…Increasingly high levels of use have been reported in some European countries, notably the United Kingdom, Germany, the Netherlands, Spain and some central and eastern European countries Korf and Wurth, 1995;Pompidou Group, 1997). Research also suggests that physical and psychological morbidity from this drug is increasing (Cassidy and Ballard, 1994;McGuire et al, 1994;Series et al, 1994;Williamson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%